2023
DOI: 10.1038/s41467-023-42491-0
|View full text |Cite
|
Sign up to set email alerts
|

Unappreciated subcontinental admixture in Europeans and European Americans and implications for genetic epidemiology studies

Mateus H. Gouveia,
Amy R. Bentley,
Thiago P. Leal
et al.

Abstract: European-ancestry populations are recognized as stratified but not as admixed, implying that residual confounding by locus-specific ancestry can affect studies of association, polygenic adaptation, and polygenic risk scores. We integrate individual-level genome-wide data from ~19,000 European-ancestry individuals across 79 European populations and five European American cohorts. We generate a new reference panel that captures ancestral diversity missed by both the 1000 Genomes and Human Genome Diversity Projec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Until recently, modeling substructure in genetic data has been limited to stratifying into homogeneous groups, which either ignores finer-scale substructure or cannot be applied to populations with substantial structure (e.g., genetically admixed populations) resulting in biased results or an underuse of data (often the very data that is also underrepresented in research) 75 . Here, we show that the methods contained in the Summix2 software package can detect, adjust, and even harness substructure in summary data by estimating genetic similarity to reference groups using only summary level data.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, modeling substructure in genetic data has been limited to stratifying into homogeneous groups, which either ignores finer-scale substructure or cannot be applied to populations with substantial structure (e.g., genetically admixed populations) resulting in biased results or an underuse of data (often the very data that is also underrepresented in research) 75 . Here, we show that the methods contained in the Summix2 software package can detect, adjust, and even harness substructure in summary data by estimating genetic similarity to reference groups using only summary level data.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, future studies may consider performing admixture mapping even on European‐descent individuals. Subcontinental admixture in European and European American individuals has recently been shown to influence height, LDL cholesterol, and body mass index associations with LCT , the gene responsible for human lactase production (Gouveia et al., 2023). It is clear that our current understanding of the influence of genetic admixture on phenotypes is incomplete, and further exploration of its effects in any population is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The process is ubiquitous and spans scale in space and time, from the admixture with Neanderthals around 50,000 years ago when modern humans migrated out of Africa 4 , to native Americans mixing with primarily European and African immigrants over the last 500 years to form the majority of United States ancestry 5 , and the fine-scale geographical regionalisation within a single country such as the UK 6 . The identification of chromosomal regions originating from a specific population is known as local ancestry inference (LAI) 7 , which can be used to map disease loci 8 , investigate the relationships between modern populations, improve association studies 9 , and study demographic histories 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have identified single nucleotide polymorphisms (SNPs) associated with human complex traits and diseases 11 , but the SNP frequencies are likely to be associated with particular ancestries. Local ancestry may then either be viewed as a confounder of the SNP effect 9 , or treated as a predictor as in ‘Ancestral GWAS’ 12 . In this framing, local ancestry inference examines the ancestral origin of risk loci in terms of a population and a time — for instance, risk alleles associated with multiple sclerosis originated from pastoralists dwelling on the Pontic Steppe, which were brought into Europe by the Yamnaya-related migration around 5,000 years ago 12 .…”
Section: Introductionmentioning
confidence: 99%